Structure and aggregation kinetics of vinyltriethoxysilane-derived organic/silica hybrids - Vollet, Dimas R. [UNESP]; Donatti, Dario A. [UNESP]; Awano, Carlos M. [UNESP]; Chiappim, William [UNESP]; Vicelli, Marcio R. [UNESP]; Ruiz, Alberto Ibanez [UNESP] (Wiley-Blackwell, 2010)
The aggregation kinetics of solutions of vinyltriethoxysilane-derived organic/silica hybrid species were studied by small-angle X-ray scattering (SAXS) in a strongly basic medium. The SAXS intensity was analysed by a modified Sharp-Bloomfield (SB) global function and its evolution was found to be compatible with the growth, coiling and branching of the polymeric macromolecules in solution. A form factor valid for randomly and nonrandomly branched polycondensates and for polydisperse coils of linear chains was used in the modified SB model, instead of the Debye function valid for monodisperse coils of linear chains. The aggregation kinetics are accelerated with increasing base concentration in the studied range, but all the kinetics curves can be matched to a unique curve using an appropriate time scaling factor. The aggregation kinetics suggest that physical forces (hydrothermal forces) associated with phase coarsening could be active in the aggregation process, together with diffusion mechanisms.
Keywords: aggregation kinetics; organic; silica hybrids; macromolecules; small-angle X-ray scattering